Oral health and socio-economic status among children during Syrian crisis: a cross-sectional study - Bahaa Aldin Alhaffar; Raeed Alawabdi; Leen Barakat; Chaza Kouchaji (BMC, 2019)
Abstract Background The Syrian crisis has started eight years ago and has, directly and indirectly, affected all the aspects of the Syrians lives. A lot of new war-related factors contributed to change the socio-economic status, the demographical distribution and the ability to access the public health services. Moreover, the crisis created the biggest displacement crisis both inside and outside Syria. Therefore, it is important to study the prevalence of dental caries and oral health in these specific circumstances in order to build a database to assess and compare future results of preventive programs and to assess health and social needs of the communities affected by war or crisis. The aim of this research is to Study the level of oral health among children during the Syrian crisis, as well as the relation between oral health and socioeconomic status (SES). Methods A cross-sectional study to assess the oral health of children in Damascus city by using DMFT index and other dental indices. The data were collected from ten randomly selected schools covering all the areas of Damascus city, and the final sample size was 811 children. Results DMFT index was used to assess the oral health of the children. The average number was (3.36) among all children; 14% of the sample size had a good oral health, while 86% had at least one decayed, missed, or filled tooth. There was also a strong association between SES of the child and the oral health represented as DMFT Index (P = 0.03), Pearson's correlation test displayed an inverse association between the SES and oral health (P = − 0.074). Conclusion This study highlights the impact of the Syrian crisis on the SES of the Syrian children and their oral health. Bad oral health has been recorded and it has a significant relation with the SES of the children.